New perspective for third generation percutaneous vertebral augmentation procedures: Preliminary results at 12 months - Daniele Vanni; Andrea Pantalone; Francesco Bigossi; Filippo Pineto; Danilo Lucantoni; Vincenzo Salini (Journal of Craniovertebral Junction and Spine, 2012)
Introduction: The prevalence of osteoporotic vertebral fractures (OVF) increased in the last years. Compression fractures promote a progressive spine kyphosis increase, resulting in a weight shift and anterior column overload, with OVF additional risk (domino effect). The aim of this study is to evaluate the OVF treatment outcome using Spine Jack ®, a titanium device for third generation percutaneous vertebral augmentation procedures (PVAPs). Materials and Methods: From February 2010, a prospective randomized study was performed examining 300 patients who underwent PVAP due to OVF type A1 according to Magerl/AO spine classification. Patients enrolled in the study were divided in two homogenous groups with regards to age (65-85 years), sex, and general clinical findings. Group A included 150 patients who underwent PVAP using Spine Jack ® system; the second, group B (control group), included 150 patients treated by conventional balloon kyphoplasty. Patients underwent a clinical (visual analogue scale and Oswestry disability index) and radiographic follow-up, with post-operative standing plain radiogram of the spine at 1, 6, and 12 months. The radiographic parameters that were taken into account were: Post-operative anterior vertebral body height, pre-operative anterior vertebral body height, cephalic anterior vertebral body height, and caudal anterior vertebral body height. Results: Compared to the Spine Jack ® group, the kyphoplasty group required a little longer operation time (an average of 40 min-group A vs. 45 min-group B, P < 0.05) and a greater amount of polymethylmethacrylate (4.0 mL-group A vs. 5.0 mL-group B, P < 0.05;). The post-operative increase in vertebral body height was greater in the Spine Jack ® group than in the kyphoplasty group (P < 0.05). Discussion: PVAP are based on the cement injection into the vertebral body. Vertebroplasty does not allow the vertebral body height recovery. Balloon kyphoplasty allows a temporary height restoration. Spine Jack ® has some new features compared to other systems: It is equipped with a mechanical and not a hydraulic opening control; this ensures a gradual and controlled vertebral fracture reduction. Conclusions: In our study, we demonstrated that the third generation PVAP with Spine Jack ® is able to determine a safe vertebral body height restoration compared to the conventional balloon kyphoplasty.